Karakteristik Pembakaran Campuran Batubara dan Tandan Kosong Kelapa Sawit (TKKS) Menggunakan Analisis Termogravimetri Deferensial Temperatur (TG-DTA) - Wiwie Chaeruni; Hadiyanto Hadiyanto; Cahyadi Cahyadi (G-Tech: Jurnal Teknologi Terapan, 2024)
The Indonesian government's commitment to reducing emissions and greenhouse gases by using biomass as an alternative fuel. This research aims to analyze and evaluate the combustion characteristics using TG-DTA (Thermo Gravimetric-Differential Thermal Analyzer) with coal, empty fruit bunches (EFB), and a mixture of EFB and coal. Sample testing was carried out with four variations of mixtures of EFB and coal, namely 10%, 20%, 30% and 40%, carried out in nitrogen and air media at a constant heating rate of 20 °C/minute and constant gas flow. 20 mL/minute and calculate the weight loss as the temperature increases to 900 °C. The combustion properties were analyzed by observing the combustion profile graph to obtain thermogravimetric (DTG) derivative data to obtain the initiation temperature, combustion temperature, maximum combustion temperature, combustion reactivity, and energy activity of EFB, and mixture.